Teaching Taboo Topics: Menstruation in a Global Context - Kushwaha, Madhu; Maring, Elisabeth Fost (Radical Teacher, 2024)
Inadequate menstrual health education is a global public health issue. An innovative Global Classroom course, Teaching Menstrual Health: Dispelling Myths and Misconceptions, is situated at the intersection of gender, culture, and health. The course engages students from India and the U.S. in project-based learning on menstrual health and misconceptions that impact individuals and communities. Linking the fields of public health and education, students engage in lectures and discussions that address power imbalances and build cultural competency before working collaboratively on projects to address stigma around menstruation. The course was designed to address colonial narratives that marginalize menstruators and undermine women’s health. Student experiences are quoted to demonstrate how the five course development strategies create action for menstrual and reproductive justice.